Immune correlates of clinical parameters in patients with HPV-associated malignancies treated with bintrafusp alfa. Issue 4 (13th April 2022) - Tsai, Yo-Ting; Strauss, Julius; Toney, Nicole J; Jochems, Caroline; Venzon, David J; Gulley, James L; Schlom, Jeffrey; Donahue, Renee N
Abstract : Purpose: Bintrafusp alfa is a bifunctional agent consisting of an anti-human PD-L1 antibody linked to two TGFβRII. It is designed to act both as a checkpoint inhibitor and to 'trap' TGFβ in the tumor microenvironment. Phase I and II clinical studies demonstrated clinical activity in patients with a range of human papillomavirus (HPV)-associated cancers. The purpose of the studies reported here was the interrogation of various aspects of the peripheral immunome in patients with HPV-associated cancers, both prior to and early in the treatment regimen of bintrafusp alfa to better understand the mode of action of the agent and to help define which patients are more likely to benefit from bintrafusp alfa treatment. Patients and methods: The peripheral immunome of patients (n=65) with HPV + malignancies was analyzed both prior to treatment with bintrafusp alfa and day 14 post-treatment for levels and changes in (1) 158 different immune cell subsets, (2) multiple plasma soluble factors including analytes reflecting immune stimulatory and inhibitory status, (3) complete blood counts, and in a subset of patients (4) TCR diversity and (5) HPV-specific T-cell responses. Results: Interrogation of the peripheral immunome prior to bintrafusp alfa treatment revealed several factors that associated with clinical response, including (1) higher levels of sCD27:sCD40L ratios, (2) lower levels of TGFβ1 and 12 additional factors associated with tumor mesenchymalization, and (3) higher CD8 + T cell:MDSC ratios. Analysis at 2 weeks post bintrafusp alfa revealed that eventual clinical responders had fewer increases in IL-8 levels and the neutrophil to lymphocyte ratio, and higher levels of HPV-16 specific CD8 + T cells. This study also provided information concerning differences in the peripheral immunome for patients who were naïve versus refractory to prior checkpoint inhibition therapy. While preliminary, two multivariate models developed predicted clinical benefit with 76%–91% accuracy. Conclusions: These studies add insight into the mechanism of action of bintrafusp alfa and provide evidence that the interrogation of both cellular and soluble components of the peripheral immunome of patients with HPV-associated malignancies, either prior to or early in the therapeutic regimen, can provide information as to which patients are more likely to benefit with bintrafusp alfa therapy.